Cartografías de repudio en Argentina - Cascallana, Lorena Silvana (2019)
This dissertation develops a questioning about the ways some Argentine repressors´children repudiate the actions of their parents. Approached with the cartographic methodology, three types of repudiation are enunciated: disaffiliating modality, disobedient modality, and bridge modality, rescuing counterpoints and approximations among them. These three types of repudiation are raised as possible responses to the hypothesis raised that horrors are not inherited. It is the objective of this work, to focus, and thus make visible the actions of desire, which are sustained in an active and ethical policy, demonstrating some subjectivities of the repressors´children , who repudiate the actions of their parents, and thus develop a new lineage, creating other modes of existence , which exempt them from the horror that they have had to live with, due to being children of executioners